Member Welfare as a Driving Force for the Survival of Agricultural Institutions: Empirical Evidence from Thailand’s Major Rubber-Producing Areas - Hlonglaloeng, Khomsan; Sukhabot, Sasiwemon; Rinthaisong, Idsaraat (Journal of Cultural Analysis and Social Change, 2025)
This study examined the impact of member welfare programs on the business survival of agricultural institutions in Southern Thailand using structural equation modeling (SEM). Data were collected from 450 cooperative executives representing 150 cooperatives across five southern provinces. The welfare program framework was developed through in-depth interviews with 30 cooperative leaders. Results from exploratory and confirmatory factor analyses indicated that both member welfare provision and business survival were unidimensional constructs, with all indicators showing factor loadings greater than 0.60. Reliability and convergent validity met acceptable thresholds, with composite reliability (CR) and average variance extracted (AVE) values of 0.843 and 0.519 for member welfare, and 0.901 and 0.506 for business survival, respectively. The structural model demonstrated an excellent fit with the empirical data (χ² = 88.907, df = 76, p = 0.148, RMSEA = 0.019, CFI = 0.997, TLI = 0.997, SRMR = 0.025). Member welfare programs had a significant positive effect on business survival (β = 0.574, p < 0.001), explaining 33% of the variance. The findings confirm that welfare provision is a crucial determinant of the business survival of agricultural institutions. Furthermore, the study proposes an appropriate welfare model tailored to the southern agricultural context, which can serve as a practical framework to strengthen the survival of cooperative institutions in the future.